The Determinants of Inclusive Logistics on Foreign Direct Investment: Comparative Evidence from Upper and Lower Middle-Income Countries - Irna Kumala; Heru Subiyantoro; Jooner Rambe (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study investigates the impact of inclusive logistics factors on foreign direct investment (FDI) in two groups middle income countries, upper middle and lower middle. This study was conducted in 24 countries using panel data analysis with FMOLS, DOLS, and dynamic GMM from 2007-2023. Six dimensions of the Logistics Performance are customs, infrastructure, international shipments, logistics competence, tracking & tracing, and timeliness are examined as determinants of foreign direct investments inflows. The results reveal that timeliness significantly drives FDI in UMI countries, while infrastructure is the main determinant in LMI countries. This study highlights heterogeneity in logistics performance related to FDI linkages across countries development stages is consistent with the Investment Development Path theory.